2012
DOI: 10.3892/mmr.2012.1135
|View full text |Cite
|
Sign up to set email alerts
|

Hirsutine, an indole alkaloid of Uncaria rhynchophylla, inhibits inflammation-mediated neurotoxicity and microglial activation

Abstract: Chronic microglial activation endangers neuronal survival through the release of various pro-inflammatory and neurotoxic factors. As such, negative regulators of microglial activation have been considered as potential therapeutic candidates to reduce the risk of neurodegeneration associated with inflammation. Uncaria rhynchophylla (U. rhynchophylla) is a traditional oriental herb that has been used for treatment of disorders of the cardiovascular and central nervous systems. Hirsutine (HS), one of the major in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…We have recently shown that LPS at 10 mg ml À1 prominently reduced immunoreactivity of NeuN, a neuronal-specific marker, together with elevated propidium iodide (PI) fluorescence in OHSCs. 28 In the same experimental condition, the immunoreactivity for Iba1, a microglia-specific marker, did not seem to be reduced after the LPS insult (data not shown). After stimulation with LPS for 72 h, the culture medium was collected and subjected to nitrite and cytokine assays and was subsequently replaced with fresh serum-free medium containing PI.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…We have recently shown that LPS at 10 mg ml À1 prominently reduced immunoreactivity of NeuN, a neuronal-specific marker, together with elevated propidium iodide (PI) fluorescence in OHSCs. 28 In the same experimental condition, the immunoreactivity for Iba1, a microglia-specific marker, did not seem to be reduced after the LPS insult (data not shown). After stimulation with LPS for 72 h, the culture medium was collected and subjected to nitrite and cytokine assays and was subsequently replaced with fresh serum-free medium containing PI.…”
Section: Discussionmentioning
confidence: 84%
“…The concentration of LPS required for neurotoxicity in tissue cultures was higher than that used in primary microglial cultures. We have recently shown that LPS at 10 µg ml −1 prominently reduced immunoreactivity of NeuN, a neuronal‐specific marker, together with elevated propidium iodide (PI) fluorescence in OHSCs . In the same experimental condition, the immunoreactivity for Iba1, a microglia‐specific marker, did not seem to be reduced after the LPS insult (data not shown).…”
Section: Resultsmentioning
confidence: 94%
“…In vitro investigations have shown that Uncaria plants ameliorate amyloid-β-induced neuronal death, methamphetamine-induced rat cortical neurons death, glutamate-induced PC12 cell death and LPS-induced hippocampal cell death, etc (Jung et al, 2013;Kawakami et al, 2011;Mo et al, 2006;Xian et al, 2012b). In vivo experiments have revealed that Uncaria plants improve learning and memory impairments and dementia-like behaviors in various animal models (Fujiwara et al, 2011;Xian et al, 2011;Xian et al, 2014a).…”
Section: Effects On the Central Nervous Systemmentioning
confidence: 93%
“…Our recent work focusing on an anti-inflammatory extract of UR isolated 11 oleanane and ursane triterpenic acids, three of which showed weak inhibitory effects on LPS-induced NO production in RAW264.7 cells [22]. The potential neuroprotective function of UR may be due to indole alkaloids [23][24][25][26]. Indole alkaloids are used as biomarkers for the quality control of Gou-Teng [27,28].…”
Section: Introductionmentioning
confidence: 99%